2020
DOI: 10.3390/su12239908
|View full text |Cite
|
Sign up to set email alerts
|

Prioritization of Cartagena Coastal Military Batteries to Transform Them into Scientific, Tourist and Cultural Places of Interest: A GIS-MCDM Approach

Abstract: This study presents a combination of multi-criteria decision-making (MCDM) methodologies with geographic information systems (GIS) to carry out a prioritization of obsolete military coastal batteries with the aim of transforming them into touristic, scientific, and cultural places of interest. The study area is located in the Municipality of Cartagena, in Southeast Spain. Such a prioritization requires taking into account transport criteria (distance to roads or train stations), infrastructure criteria (distan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Sánchez-Lozano and Rodríguez [38] use the Fuzzy Reference Ideal Method (FRIM) for the selection of the best military advanced training aircraft in the Spanish Air Force. Sánchez-Lozano et al [39] showed a combination of the MCDM methodology (the AHP and TOPSIS methods) with the geographic information systems (GIS) used to carry out prioritization of obsolete military coastal batteries with the aim of transforming them into touristic, scientific, and cultural places of interest. De Almeda et al [40] used the Simple Aggregation of Preferences Expressed by Ordinal method Vectors-Multi Decision Makers (SAPEVO-M) and VIKOR methods to select the most suitable city as the headquarters of the Second Fleet of the Brazilian Navy.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Sánchez-Lozano and Rodríguez [38] use the Fuzzy Reference Ideal Method (FRIM) for the selection of the best military advanced training aircraft in the Spanish Air Force. Sánchez-Lozano et al [39] showed a combination of the MCDM methodology (the AHP and TOPSIS methods) with the geographic information systems (GIS) used to carry out prioritization of obsolete military coastal batteries with the aim of transforming them into touristic, scientific, and cultural places of interest. De Almeda et al [40] used the Simple Aggregation of Preferences Expressed by Ordinal method Vectors-Multi Decision Makers (SAPEVO-M) and VIKOR methods to select the most suitable city as the headquarters of the Second Fleet of the Brazilian Navy.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Sánchez-Lozano et al (2015) selected military training aircraft for the Spanish Air Force, through hybrid modeling composed of AHP, TOPSIS and Fuzzy Logic. Sánchez-Lozano et al (2020) conducted a study to prioritize obsolete military coastal batteries, to transform them into places of tourist interest in Spain, through the application of the GIS, AHP and TOPSIS methods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Because the System has a trivial solution, (1) must be a singular matrix. Being (3) an equation of degree n, called the characteristic equation of M, which is equal to 0 if λ is replaced by M, producing a matrix equation, where the roots are the characteristic values that were obtained from the priority vector, from of the solution of the corresponding systems of equations [42], [43].…”
mentioning
confidence: 99%